2004
DOI: 10.1073/pnas.0307132101
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid of APOBEC3G controls its species-specific interaction with virion infectivity factor (Vif)

Abstract: The virion infectivity factor (Vif) accessory protein of HIV-1 forms a complex with the cellular cytidine deaminase APOBEC3G (apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3G) to block its antiviral activity. The antiviral property of APOBEC3G is conserved in several mammalian species, but the ability of Vif to block this activity is species-specific. HIV-1 Vif blocks human APOBEC3G but does not block the mouse or African green monkey (AGM) enzyme. Conversely, SIVAGM Vif blocks the antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
305
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(325 citation statements)
references
References 30 publications
15
305
2
3
Order By: Relevance
“…It also contributed to explain the narrow host range of HIV-1 that shows spreading replication only in humans and chimpanzees (49,59). Such defined interactions of Vif proteins with cognate A3 proteins had been shown so far only for HIV, SIV, and Feline immunodeficiency virus (49,58,74). But the discovery of the Vif-A3 interaction also highlighted the conundrum of "simple" mammalian retroviruses like Mo-MLV and Mouse mammary tumor virus and their survival without accessory genes like the vif gene (45,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 98%
“…It also contributed to explain the narrow host range of HIV-1 that shows spreading replication only in humans and chimpanzees (49,59). Such defined interactions of Vif proteins with cognate A3 proteins had been shown so far only for HIV, SIV, and Feline immunodeficiency virus (49,58,74). But the discovery of the Vif-A3 interaction also highlighted the conundrum of "simple" mammalian retroviruses like Mo-MLV and Mouse mammary tumor virus and their survival without accessory genes like the vif gene (45,(64)(65)(66).…”
Section: Discussionmentioning
confidence: 98%
“…Abrogation of Vif binding by A3G could also confer resistance to Vif-dependent degradation, as was observed for the D128K mutant (27)(28)(29)(30). It therefore seemed prudent to determine whether Arg substitutions at A3G residues 297, 301, 303, and 334 would in any way interfere with A3G's ability to bind Vif.…”
Section: Resultsmentioning
confidence: 99%
“…The region in A3G responsible for binding to HIV-1 Vif was initially identified by comparative studies of the species specificity of A3G degradation by Vif. Thus, a single amino acid difference in hA3G, Asp at position 128 versus Lys in the A3G of African green monkeys (A3G agm ), determines species specificity by influencing Vif-A3G binding (27)(28)(29)(30). Furthermore, extensive site-directed mutagenesis revealed that the 128 DPD 130 motif of A3G, located near the first Zn cluster, is crucial for direct binding to HIV-1 Vif.…”
mentioning
confidence: 99%
“…Recent studies demonstrated that single aminoacid substitutions in the human TRIM5a and human APOBEC3G could render the human proteins potent restriction factors against HIV-1. [33][34][35][36][37] Thus, as suggested by Yap et al, 37 we can use the R332P derivative of human TRIM5a, in combination with the Vif-insensitive, K128D derivative of human APOBEC3G, as ideal alternatives to reduce host immune response to the restriction factors.…”
Section: Co-expression Of Agm-apobec3g and Agm-trim5a Efficiently Blomentioning
confidence: 99%
“…In contrast, HIV-1 Vif cannot neutralize agm-APOBEC3G. 34 We therefore examined the anti-viral effects of agm-APOBEC3G on HIV-1 replication. The HA-tagged agm-APOBEC3G-expressing retroviral vector, pBabe-puroaA3G, was produced by cloning the EcoRI-XhoI fragment of pc-AGM-APOBEC3G-HA into the EcoRI-SalI sites of pBabe-puro.…”
Section: Co-expression Of Agm-apobec3g and Agm-trim5a Efficiently Blomentioning
confidence: 99%